Extracorporeal membrane oxygenation outcomes in children with hemophagocytic lymphohistiocytosis. (March 2017) - Cashen, Katherine; Chu, Roland L; Klein, Justin; Rycus, Peter T; Costello, John M
Introduction: Pediatric patients with hemophagocytic lymphohistiocytosis (HLH) may develop refractory respiratory or cardiac failure that warrants consideration for extracorporeal membrane oxygenation (ECMO) support. The purposes of this study were to describe the use and outcomes of ECMO in pediatric HLH patients, to identify risk factors for hospital mortality and to compare their ECMO use and outcomes to the ECMO population as a whole. Methods: Pediatric patients (⩽ 18 years) with a diagnosis of HLH in the Extracorporeal Life Support Organization (ELSO) Registry were included. Results: Between 1983 and 2014, data for 30 children with HLH were available in the ELSO registry and all were included in this study. All cases occurred in the last decade. Of the 30 HLH patients, 24 (80%) had a respiratory indication for ECMO and six (20%) had a cardiac indication (of which 4 were E-CPR and 2 cardiac failure). Of the 24 respiratory ECMO patients, 63% were placed on VA ECMO. Compared with all pediatric patients in the ELSO registry during the study period (n=17, 007), HLH patients had worse hospital survival (non-HLH 59% vs HLH 30%, p=0.001). In pediatric HLH patients, no pre-ECMO risk factors for mortality were identified. The development of a hemorrhagic complication on ECMO was associated with decreased mortality (p=0.01). Comparing HLH patients with respiratory failure to patients with other immune compromised conditions, the overall survival rate is similar (HLH 38% vs. non-HLH immune compromised 31%, p=0.64). Conclusions: HLH is an uncommon indication for ECMO and these patients have increased mortality compared to the overall pediatric ECMO population. These data should be factored into decision-making when considering ECMO for pediatric HLH patients.